In vitro slow-growth conservation, acclimatization, and genetic stability of virus-free apple plants - Xian Lu; Pengpeng Sun; Ruihan Liu; Caiwen Wang; Lu Tong; Muhammad Mobeen Tahir; Xiaoyan Ma; Junhua Bao; Dong Zhang; Minrui Wang; Na An (Horticulture Advances)
Abstract In vitro slow-growth storage has long played an important role in maintaining valuable horticultural materials. It is particularly applicable to the conservation of virus-free materials recovered from meristem culture or shoot-tip cryotherapy. In this study, the apple cultivar ‘Yanfu-6’ and the rootstock genotype ‘Qingzhen-1’ obtained from a virus disinfection program were compared during the establishment of in vitro slow-growth storage programs. At room temperature (25℃), combining with 4.5% sucrose or 0.5% mannitol, extended the conservation period of ‘Yanfu-6’ and ‘Qingzhen-1’to 5 and 9 months, respectively. Decreasing the temperature to 12℃ led to further reduced shoot growth, extending the conservation period to 9 months for ‘Yanfu-6’, while more than 80% of ‘Qingzhen-1’ shoots could be recovered after one year of storage. Similarly, high rooting and acclimatization success levels were obtained for ‘Qingzhen-1’ after one-year storage at 12℃, as well as for the plants that underwent monthly subcultures, but not for ‘Yanfu-6’. The inability to root in ‘Yanfu-6’ was overcome by micrografting onto rootstock ‘Qingzhen-1’, which resulted in a rooting percentage of 83% and an acclimatization success of 77%. In the analysis of genetic stability by next-generation sequencing, reduced levels of single nucleotide polymorphism (SNPs) and insertions and deletions (InDels) were detected in ‘Qingzhen-1’ shoots recovered after one-year storage at 12℃, as compared with shoots that underwent regular subcultures. These results highlight the use of in vitro slow-growth program assisted with micrografting for the conservation of valuable horticultural species.